Model Pemberdayaan Inklusif Bagi Atlet Disabilitas : Integrasi Inklusi Sosial dan Psychological Well-Being - Joko Muliyono; Annisya’ Annisya; Abdul Azis (Journal of Creative Student Research, 2026)
This study aims to develop an inclusive empowerment model for athletes with disabilities that integrates aspects of social inclusion in an effort to achieve peak performance. The study employs a qualitative approach based on a constructivist paradigm and a stage-based conceptual model development design. Analysis was conducted using thematic analysis and conceptual synthesis to identify, group, and integrate key concepts into a comprehensive model. The results of the study indicate that the inclusive empowerment model consists of six main stages: E-Empower (education and empowerment), E-Train (training and performance development), E-Include (social inclusion), E-Mind (psychological strengthening), E -Career (career development), and E-Eval (evaluation and monitoring), which systematically lead to the achievement of peak performance. This model emphasizes that the optimal performance of athletes with disabilities is determined not only by physical aspects but also by social support, mental readiness, and career sustainability. This study contributes to integrating the concepts of empowerment and social inclusion into sports performance development. This model can serve as a reference for designing more inclusive, adaptive, and sustainable athlete development programs for athletes with disabilities.